Stability of bucket movement and directionof movement of the continuous unit to form the underlying layer of the road - V. A. Nikolaev (Вестник СибАДИ, 2021)
Introduction. The unit of continuous action for the formation of the underlying layer is designed to increase labor productivity in the construction of roads and other objects, for the construction of which it is necessary to remove the upper layer of soil. The working bodies of the unit are buckets that cut and transport soil. To balance these forces and moments in the transverse-vertical plane, relative to the direction of movement of the buckets, support bars with support hydraulic cylinders are used. To create and regulate the pressure in the support hydraulic cylinders, two hydraulic pneumatic accumulators for controlling the supporting strips are installed on the power device. Part of the forces and moments through the supporting strips, support hydraulic cylinders, the frame of the working part of the unit is transmitted to the energy device that serves to drive the unit. During the operation of the unit, the resistance of the soil to cutting changes continuously. Therefore, the forces and moments transmitted to the energy device change. During operation, the stability of the rectilinear course of the unit is necessary. To ensure the stability of the movement of buckets and the direction of movement of the unit, you should first consider the process of filling the buckets with soil.The method of research. On the basis of the constructive layout, the number of buckets filled with soil was revealed. Suppose the filling of buckets with soil occurs gradually and evenly. Hence, an increase in the load on the right and left support bar was revealed by each subsequent bucket as it is filled. By adding the vertical forces, the value and position of the total load on the supporting bars are determined. The resistance to the movement of the left and right wheels of the working part of the unit, due to the load from the buckets to the supporting strips, the gravity of the raised soil, the gravity of the working part of the unit, is determined. The total horizontal force, the impact of soil on the buckets, directed along the course of the unit, was revealed. The method of calculating the position of the thrust vector of the energy device is given.Results. On the basis of the developed technique, the diameters of the support hydraulic cylinders and the nominal pressure in the hydraulic pneumatic accumulators of the control of the right and left support strips were determined. A constructive layout of the hinged energy device and a system for automatic adjustment of the position of the thrust vector of the energy device depending on the properties of the developed soil is proposed.Conclusion. On the basis of theoretical studies, the diameters of the support hydraulic cylinders and the nominal pressure in the hydraulic pneumatic accumulators of the control of the right and left support strips were calculated. An example of calculating the position of the thrust vector of an energy device is given. The constructive arrangement of the system of automatic adjustment of the position of the thrust vector of the energy device depending on the properties of the developed soil and the general layout of the energy device is proposed. The conducted theoretical studies allow to ensure the stability of the movement of buckets and the direction of movement of the continuous unit for the formation of the underlying layer of roads.